Double diffusive MHD stagnation point flow of second grade fluid in non-Darcy porous media under radiation effects - Walid Aich; Amir Abbas; Adebowale Martins Obalalu; Walid Hassen; Lotfi Ben Said; Rejab Hajlaoui; Lioua Kolsi (Scientific Reports)
Abstract Non-Newtonian fluids are also widely used in a variety of scientific, engineering, and industrial domains, including the petroleum sector and polymer technologies. They are vital in the development of drag-reducing agents, damping and braking systems, food manufacturing, personal protective equipment, and the printing industry. Fluid movement and transport via porous materials draw a lot of attention; they are important in science and technology. Porous media appear in a variety of high-speed phenomena and devices, including catalytic converters, condensers, and gas turbines. Due to above physical significance, the influence of solar radiation and Lorentz forces on the behavior of non-Newtonian second-grade fluids in a Darcy-Forchheimer porous medium at a stagnation point is tackled in this study on both assisting and opposing flow regimes. A study on thermal diffusion or the Soret effect and diffusion-thermo or the Dufour effects are included in the research. Mathematical models are developed for the current situation and translated into a set of ordinary differential equations that are solved using MATLAB’s bvp4c. The data reveal that raising the second-grade fluid reduces the velocity profile while increasing the temperature and concentration profiles in both assisting and opposing flows. In both flowing regimes, increasing the porous medium parameter increases velocity while decreasing temperature. The descending trends in the velocity profiles with respect to the Forchheimer and Prandtl numbers occurs for both assisting and opposing flows. The assisting flow shows higher profiles, values compared to the opposing flow. Results show that increasing second- grade fluid parameter causes the increase in skin friction, Nusselt number and Sherwood number. The results of the current modeled problems are compared with already published results and it has been concluded that there is sufficient agreement between both of them, indicating the validity and accuracy of the present results.